ANALISIS INTERAKSI POLITIK DAN HUKUM DALAM PROSES PEMBENTUKAN PERATURAN DAERAH (PERDA) PAJAK DAN RETRIBUSI DAERAH - Wisma Happy (VERITAS, 2016)
The interaction of politics and law in the process of establishing regionalregulation (Perda) taxes and levies as the implementation of Law No. 28 Year2009 on Local Taxes and and Levies (process each influences the other, and eachrequest and giving and mutual intervention between parties which has legislativepowers in the process of forming Regulation) occur in every stage of the formationprocess of the law. But political interaction in the formation process is an intensiveregulation occurs at the stage of discussion of the draft law, particularly so duringthe meeting between a special committee of Parliament with the team workingunits (SKPD) / executive team.